2017
DOI: 10.1088/1361-648x/aa6832
|View full text |Cite
|
Sign up to set email alerts
|

Search for unconventional superconductors among the YTE2Si2compounds (TE  =  Cr, Co, Ni, Rh, Pd, Pt)

Abstract: Motivated by the recent discovery of exotic superconductivity in YFeGe we undertook reinvestigation of formation and physical properties of yttrium-based 1:2:2 silicides. Here we report on syntheses and crystal structures of the YTE Si compounds with TE  =  Cr, Co, Ni, Rh, Pd and Pt, and their low-temperature physical properties measurements, supplemented by results of fully relativistic full-potential local-orbital minimum basis band structure calculations. We confirm that most of the members of that family c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 44 publications
(51 reference statements)
2
11
0
Order By: Relevance
“…Further interest in this material derives from theoretical proposals for the superconducting state, which include s ± [3] or triplet pair wavefunctions [4] and from its striking similarities to some of the iron pnictide superconductors [8,9]. Moreover, several structurally and electronically related materials have recently been examined, some of which were found to superconduct at low temperatures [10][11][12][13], including a new iron-based superconductor, LaFeSiH [14].…”
mentioning
confidence: 99%
“…Further interest in this material derives from theoretical proposals for the superconducting state, which include s ± [3] or triplet pair wavefunctions [4] and from its striking similarities to some of the iron pnictide superconductors [8,9]. Moreover, several structurally and electronically related materials have recently been examined, some of which were found to superconduct at low temperatures [10][11][12][13], including a new iron-based superconductor, LaFeSiH [14].…”
mentioning
confidence: 99%
“…Since our DTA analysis of polycrystalline YPd 2 Si 2 (reported in ref ) has shown that the compound forms at about 1150 °C, we considered the binary compound PdSi with melting temperature of about 900 °C as an alternative flux for synthesizing single-crystalline YPd 2 Si 2 . In the first step, high-purity elemental Pd and Si were arc-melted under protective purified-argon atmosphere to form equiatomic binary compound PdSi.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…The findings reported for YFe 2 Ge 2 motivated us to perform systematic reinvestigation of other d-electron 1:2:2 silicides and germanides. Among the compounds being studied in this project is YPd 2 Si 2 , which has been briefly mentioned in the literature as a superconductor . Also in our recent report on crystal structure and basic physical properties of Y TE 2 Si 2 systems ( TE = transition element), we have only briefly described polycrystalline samples of YPd 2 Si 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8), we found that both of compounds adopted the tetragonal ThCr2Si2-type structure having three-dimentional electron-like and hole-like multiband FS's as most of the same type compounds have 45,46 . Finally, the two compounds appear to be typical of superconductors mediated by phonons (BSC-type superconductor) exhibing a superconductivity at low temperature (however, it is high compared to another compounds having the same structure) and it is not required any special dimensionality of Fermi surface requiring possible nesting vector which can favor electron's pairscoming from different conduction band 47 .…”
Section: A Comparison With Experimentsmentioning
confidence: 99%